Cadmium accumulation and transfer in yellowish-brown and limestone soils of five potato varieties based on a pot experiment in the central Hanjiang River basin - Qi, Xin; Luo, Kai; Li, Yuqi; Zhang, Yi; Fang, Yuan; Yang, Meiling (Frontiers in Sustainable Food Systems, 2024)
Introduction The contamination of farmland soil with the heavy metal cadmium (Cd) has consistently been a globally recognized environmental issue, especially with the rapid development of the central part of the Hanjiang River basin. The Cd contamination has become increasingly serious, and the accumulation and translocation of Cd in the soil-crop system warrant further research. Methods In this study, representative yellowish-brown soil and limestone soil from Hubei Province in China, as well as five varieties of potato (Solanum tuberosum L), were selected to investigate Cd accumulation and transfer regulation from soil to plants using pot tests at varying Cd concentration levels. Results and discussion For Eshu-12, Favorita, Huashu-6, Mira, and Zhongshu-5, the accumulation capacity of Cd in different parts exhibits a consistent pattern: Cdroot > Cdstem > Cdleaf > Cdtuber. The potato varieties exhibited distinct differences in Cd concentration, as follows: CdFavorita > CdMira > CdEshu-12 > CdHuashu-6 > CdZhongshu-5. The yellowish-brown soil demonstrated a higher accumulation and lower transport capacity to the plants of Cd, while limestone soil exhibited the opposite trend. The bio-concentration factor and transfer coefficients in yellowish-brown soil revealed significant (p < 0.05) accumulation and transformation of Cd in potatoes. Conclusion and recommendations This significant accumulation of Cd posed a higher risk of transfer through the food chain. Therefore, in the Hanjiang River basin, where Cd contamination is a concern, the cultivation of potatoes in limestone soil is more advisable than yellowish-brown soil to mitigate food safety risks.